Frontispiece: A Lanthanide MOF Thin‐Film Fixed with Co3O4 Nano‐Anchors as a Highly Efficient Luminescent Sensor for Nitrofuran Antibiotics. Issue 43 (1st August 2017) - Zhang, Feng; Yao, Hua; Chu, Tianshu; Zhang, Gaowei; Wang, Yi; Yang, Yangyi
Abstract : A luminescence sensor based on an Ln–metal–organic framework (MOF) thin film was designed and fabricated on the cost‐effective stainless steel wire mesh by Co3 O4 nano‐anchors fixation method. This thin‐film sensor turned out to be highly selective and sensitive to nitrofuran antibiotics, and could be reused in a consecutive testing process. It provides a platform for rapid and convenient detection of nitrofuran antibiotics. For more information, see the Full Paper by Y. Yang et al. onpage 10293 ff.